From Chalkboards to Chatbots: Revolutionizing Education with AI-Driven Learning Innovations - Putri, Dinda Febrianti; Sain, Zohaib Hassan (Educative: Jurnal Ilmiah Pendidikan, 2025)
Education is undergoing a major paradigm shift with the emergence of artificial intelligence (AI) as a driver for transforming teaching methods. This research explores the role of AI in transforming education, particularly in the transition from traditional methods such as whiteboards to more interactive learning systems based on AI chatbots. Using a qualitative approach, this research collects data through interviews with educators, students, and educational observers and analysis of related literature. The findings show that applying AI increases student engagement and creates a more personalized, flexible, and adaptive learning experience. One significant result is that AI allows students to learn at their own pace and style, while teachers can focus more on developing an in-depth curriculum. This research provides new insights into the potential of AI to improve the quality of learning and expand access to education in the digital era while inspiring the adoption of technology in various educational contexts.